Domestic violence - identification of the phenomenon. Literature review - Wójcicka, Anna; Stodulska-Blaszke, Aldona (Current Problems of Psychiatry, 2011)
Violence against family members is a very common phenomenon, it has been always present virtually and in all societies. For long too aggressive behaviors have been punishable and subject to the courts jurisdiction. Official reports, survey data and clinical studies show high rates of prevalence for each form of abuse of family members. Domestic violence affects mostly women and takes place in all social classes, and the role of women rooted in the community perception leads to a trivialisation of domestic violence. Estimates of the prevalence of violence are different and can be explained in different ways. Underestimation of the extent of domestic violence can be explained inter alia by the fact that victims of violence want to protect the integrity of the family or are convinced that this is a family matter, and that any disagreements should be resolved within the family. Often, social acceptance of domestic violence as a natural phenomenon reinforces the fear of disclosure of the facts. The results obtained are also dependent on many factors including the applied research methodology, the definition of violence, the sources of information. Research results also depend on the approach taken to domestic violence, applied the tools of measurement and research methodology.